Minimum Standards for the Protection of Human Rights under the Jurisdiction of the European Court - Arakelyan, Arpine; Khachatryan, Ashot (ՀՀ ԳԱԱ)
Within the framework of this Article, an attempt was made to establish the legal notion of human rights protection standards and consider the applicability of the latter in relation to the judgments of the European Court of Human Rights. Սույն հոդվածի շրջանակներում հեղինակների կողմից փորձ է արվել սահմանել մարդու իրավունքների պաշտպանության իրավական չափորոշիչներ եզրույթը և դիտարկել վերջինիս կիրառելիությունը Մարդու իրավունքների եվրոպական դատարանի վճիռների նկատմամբ: В рамках данной статьи со стороны авторов была сделана попытка установить правовое заключение стандартов защиты прав человека и рассмотреть применимость последнего по отношению к постановлениям Европейского суда прав человека.
Keywords: Social and Humanitarian Sciences